Oxidation-assisted alkaline precipitation: the effect of H2O2 on the size of CuO and FeOOH nanoparticles. Issue 51 (20th September 2019) - Eggermont, Sam G. F.; Rua-Ibarz, Ana; Tirez, Kristof; Dominguez-Benetton, Xochitl; Fransaer, Jan
Abstract : H2 O2 was demonstrated to narrow the size distribution and decrease the size of CuO and hydrous FeOOH (2-line ferrihydrite) nanoparticles under conditions of high supersaturation. Abstract : H2 O2 was demonstrated to narrow the size distribution and decrease the size of CuO and hydrous FeOOH (2-line ferrihydrite) nanoparticles under conditions of high supersaturation. We introduce oxidation-assisted alkaline precipitation (Ox-AP) and compare it to traditional alkaline precipitation (AP). While for AP, a metal salt solution ( e.g., CuCl2 ) is mixed with an alkali ( e.g., NaOH), for Ox-AP, the more reduced form of that metal salt solution ( e.g., CuCl) is simultaneously mixed with that alkali and an oxidant ( e.g., H2 O2 ). The resulting precipitates were characterized with SEM, XRD, DLS and single particle ICP-MS and shown to be nanoparticles (NPs). Ox-AP CuO NPs were up to 3 times smaller than AP NPs. Ox-AP FeOOH NPs were up to 22.5% smaller than AP NPs. We discuss and propose a possible mechanism of Ox-AP through careful consideration of the known reaction chemistry of iron and copper. We propose that an increased monomer formation rate enhances the nucleation rate, which ultimately results in smaller particles with a more narrow distribution. The more distinct effect of Ox-AP on copper, was attributed to the fast formation of the stable CuO monomer, compared to AP, where the Cu(OH)2 and/or Cu2 (OH)3 Cl monomers are more likely formed. Although, the exact mechanism of Ox-AP needs experimental confirmation, our results nicely demonstrate the potential of using Ox-AP to produce smaller NPs with a more narrow distribution in comparison to using AP.